Le mythe de Peter Pan ou l’angoisse du temps qui passe - Amélie Maxwell (Belphégor)
In literature, it sometimes happens that a story or a character particularly catches our attention, as well as any other person’s attention, no matter what their age, gender, level of education or native culture may be. Such a degree of popularity, a power of seduction and a compelling attraction can translate itself into a single word: myth. Among these unparalleled celebrities is Peter Pan. Whether it is while reading James Barrie’s original novel, Walt Disney’s cinematographic adaptation, or Steven Spielberg’s reinterpretation, the reader/spectator can not miss the fact that Peter Pan each time relates, reveals and explains one of the greatest preoccupations of humanity: What is time? And at the heart of the myth of Peter Pan, an even more haunting question arises: Can we escape time’s hold on us? Through the palliative ways of imagination, we learn that the effects of time on Man are inevitable, but not necessarily all-consuming.